EDUKASI EFEK PENGGUNAAN GAWAI TERHADAP KESEHATAN TUBUH DAN MENTAL - Ruhsyahadati; Liana, Nana; Tri Yana, Rahma; Susanti, Melya; Helmizar, Roland; Nani Jelmila, Sri; Puspita, Dian; Tri Septiana, Vina (Jurnal Abdi Insani, 2024)
The integration of gadgets into daily life has become unavoidable, especially among children and teenagers. These devices offer numerous advantages, such as facilitating access to information and communication. However, overuse can harm physical and mental well-being. Studies have shown that excessive gadget use can cause posture issues, eye strain, obesity, and developmental problems both psychologically and socially in young individuals. To combat these negative effects, the Faculty of Medicine at Baiturrahmah University in Padang organized an educational initiative at the Babussalam Muhammadiyah Mosque. This program, aimed at elementary school students in a Ramadan boarding school, utilized interactive presentations, discussions, and quizzes to educate participants about responsible gadget use. Thirty-five students aged 10-13 attended, showing improved understanding of the adverse effects of gadget overuse and learning tips for maintaining eye health and proper posture. The students were highly engaged and appreciated the information. Overall, educating young people about the implications of gadget use enhances their awareness and promotes healthier usage habits, mitigating potential health risks.